2016
DOI: 10.12816/0027106
|View full text |Cite
|
Sign up to set email alerts
|

Normal Values of Quadriceps Angle and Its Correlation with Anthropometric Measures in a Group of Jordanians

Abstract: Objectives: To establish the normal values of Quadriceps angle(Q angle) in Jordanians according to gender and bilaterality within-subject symmetry in both extremities, and to examine its association with anthropometric measures (body height, weight, body mass index, pelvic width, and waist to hip circumference ratio).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 15 publications
0
8
1
4
Order By: Relevance
“…Choudhary et al's evaluation of 150 participants reported no relationship between these individuals' Q angles and their ages (Choudhary et al, 2019). Likewise, Tarawneh et al's study of 419 people, identified no relationship between body weight and Q angles but did find a positive correlation between individuals' BMIs and Q angles (Tarawneh et al, 2016). Many studies have reported a negative correlation between height and Q angle (Choudhary et al, 2019;Grelsamer et al, 2005;Khasawneh et al, 2019;Kwon, 1999;Tarawneh et al, 2016).…”
Section: Resultsmentioning
confidence: 97%
“…Choudhary et al's evaluation of 150 participants reported no relationship between these individuals' Q angles and their ages (Choudhary et al, 2019). Likewise, Tarawneh et al's study of 419 people, identified no relationship between body weight and Q angles but did find a positive correlation between individuals' BMIs and Q angles (Tarawneh et al, 2016). Many studies have reported a negative correlation between height and Q angle (Choudhary et al, 2019;Grelsamer et al, 2005;Khasawneh et al, 2019;Kwon, 1999;Tarawneh et al, 2016).…”
Section: Resultsmentioning
confidence: 97%
“…Quadriceps angle: the Q-angle was measured using a long-arm goniometer (Victory Model: V-T052, Zhenjian, China Mainland). 18 To do so, both the midpoint of the patella and the tibial tubercle were located and marked using a marker pen. A line was drawn connecting the anterosuperior iliac spine (ASIS) and the midpoint of the patella, and another line was drawn from the tibial tubercle to the midpoint of the patella.…”
Section: Research Protocol and Procedures For Data Collectionmentioning
confidence: 99%
“…Finally, the Q-angle was measured as the value between the intersected lines using a long-arm goniometer. 18 The Q-angle measurement has been validated as a reliable and important indicator of biomechanical function in the lower extremity, and it describes the lateral force applied to the patellofemoral joint by the contraction of the quadriceps muscle. 19…”
Section: Research Protocol and Procedures For Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations